1948
DOI: 10.1113/jphysiol.1948.sp004275
|View full text |Cite
|
Sign up to set email alerts
|

Some effects of nicotine‐like substances and their relation to sensory nerve endings

Abstract: Peripheral effects of substances acting like nicotine have already been demonstrated with certainty at two sites, the receptive area of the ganglion cell and the motor end-plate. Evidence suggesting that nicotine-like substances act at sensory nerve endings is presented in this paper. Sensory endings resemble the other sites at which nicotine is known to act in that they are places at which propagated impulses are initiated. The possibility of such nicotine-like action was suggested by Coon & Rothman's (1940) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
54
1

Year Published

1953
1953
2008
2008

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(64 citation statements)
references
References 2 publications
9
54
1
Order By: Relevance
“…A similar action of acetylcholine and of nicotine has been observed in the isolated rabbit auricles and found to be blocked by hexamethonium (Kottegoda, 1953a). The fourth is the stimulant action of acetylcholine and of nicotine on sensory nerve endings in the skin described by Brown and Gray (1948). Douglas and Gray (1953) have recently shown that this action, like that on the carotid body, is blocked by hexamethonium, but that the receptors in the skin still discharge impulses in response to touch.…”
Section: Discussionmentioning
confidence: 75%
“…A similar action of acetylcholine and of nicotine has been observed in the isolated rabbit auricles and found to be blocked by hexamethonium (Kottegoda, 1953a). The fourth is the stimulant action of acetylcholine and of nicotine on sensory nerve endings in the skin described by Brown and Gray (1948). Douglas and Gray (1953) have recently shown that this action, like that on the carotid body, is blocked by hexamethonium, but that the receptors in the skin still discharge impulses in response to touch.…”
Section: Discussionmentioning
confidence: 75%
“…The possibility must be considered that nicotine acts on the post-ganglionic fibres of the myenteric plexus in view of the fact that nicotine stimulates not only ganglion cells but also nerve fibres or endings, for instance in the skin and mesentery (Coon & Rothman, 1940;Brown & Gray, 1948).…”
Section: Plexus-free Intestinal Musclementioning
confidence: 99%
“…Some forms of pain are thought to be mediated by small myelinated fibres, and fibres of this type in cutaneous nerves are known to be excited by acetylcholine (Brown & Gray, 1948;Douglas & Gray, 1953)-a drug which causes pain when injected into the skin (Armstrong, Dry, Keele & Markham, 1953). It would be valuable to know whether the action of acetylcholine (ACh) was confined to myelinated fibres or whether it extended to the nonmyelinated fibres which are also believed to signal certain painful stimuli.…”
mentioning
confidence: 99%